Theory and Ideology of Debates on Dismissal in Spain - Valdés Dal-Ré, Fernando (2016)
This article analyzes the three major debates that have steadily been following the numerous regulatory changes, as regards dismissal, preceded the recent reform of 2012. They are: the regulation of the principle of causality and contradiction of dismissal which involves the allocation of unfair dismissal statute efficiency, reducing the cost of dismissal as a measure to combat chronic high rate of temporary employment in the Spanish industrial relations system and, finally, the argument of maintaining historical administrative authorization for lay offs of collective character. An examination of these discussions, we try to review schematically the most controversial aspects of that reform, paying particular attention to the matters of regulation and choice of the legislature by the most extreme solutions for dismissal.